OPTIMIZATION OF VILLAGE WATER MANAGEMENT: DEVELOPMENT OF SOP BP-SPAMS FOR SUKALAKSANA VILLAGE, SAMARANG, GARUT - Yuliafitri, Indri; Mulyani, Sri (LPPM Univ. Ibn Khaldun Bogor, 2025)
Sukalaksana Village, located in Samarang District, Garut, possesses abundant natural water resources. However, the community-based water management unit, BP-SPAMS, faces significant operational challenges due to the absence of standardized procedures. This community service program aims to improve the governance of clean water services by formulating context-specific Standard Operating Procedures (SOPs) and implementing digital financial recording systems. Using a Participatory Rural Appraisal (PRA) approach, the program engaged local stakeholders, including BP-SPAMS staff, BUMDes management, and village officials, in all stages from problem mapping to evaluation. The activities included field observations, focus group discussions, SOP drafting and training, as well as technical assistance through on-the-job learning. Eight tailored SOP documents were successfully developed covering core operational aspects, from water distribution and meter inspection to payment processing and financial reporting. In addition, the transition from manual to digital bookkeeping was facilitated through practical workshops. The implementation of SOPs and digital systems has led to increased efficiency, transparency, and staff professionalism. It also enhanced public trust and stakeholder participation, while opening up opportunities to replicate the initiative in other village enterprises. This program demonstrates how capacity building through structured procedures and digital tools can significantly strengthen village-level public service delivery and support sustainable development goals.